ADVANCED METHODS OF TEACHING FOREIGN LANGUAGES USING MODERN INFORMATION AND COMMUNICATION TECHNOLOGIES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In this article, the system for teaching foreign languages to the younger generation through the introduction of advanced methods of teaching foreign languages using modern information and communication technologies, the training of specialists with excellent knowledge of these languages modern style, technology and methods. Teaching foreign languages in order to create conditions and opportunities for radical improvement and, on this basis, their achievements in world civilization and wider use of world information resources, to develop international cooperation and dialogue. Issues of creation and introduction to the educational process.